« Les TIC au service du développement en Afrique » - Alain François LOUKOU (Tic & Société)
The problem associated with development by ICTs is a root of controversies. Despite the present context characterized by the intensive use of information in many activities, the contribution of ICTs to development remains contested. This has particularly been so for Africa where these tools are generally considered by their detractors as an unproductive luxury with respect to classical development priorities. Without undermining the pertinence of these arguments, this study seeks to present its weaknesses and to demonstrate, through theoretical reasoning with supporting examples, that ICTs are today a decisive factor for development in Africa, and even a prerequisite to its realisation. The study is also based on the rich literature about ICTs for development issues.